Discussion Panel HFES Technical Standards Update 2019 HFES Annual Meeting. (November 2019) - Fox, Robert R. (Bob); Kerr, Michelle; Albin, Tom; Gardner-Bonneau, Daryle; Rempel, David; Hale, Kelly; Reid, Christopher R.
HFES oversees a variety of ergonomics and human factors standards activities including standards developed within HFES (e.g. HFES 100) and standards work outside of HFES such as ANSI and ISO. This session is intended to update HFES members on the standards work that HFES is involved. This year the emphasis will be on specific new standards work on topical areas. A new ISO Technical Report on human factors in robotic, intelligent and autonomous systems (RIA) will be introduced along with the work of the HFES liaison to the US Department of Defense HF/E TAG. There will be an update on the new work of the ASTM 48.02 on exoskeletons and exosuits. The work on the revised ANSI/HFES 100 Human Factors Engineering of Computer Workstations, which is nearing completion, will be discussed. An update on the ACGIH work on ergonomics standards will be reviewed.